Paving the Road for the Adoption of Normothermic Regional Perfusion in Canada. (28th October 2021) - Basmaji, John; Weijer, Charles; Skaro, Anton; Healey, Andrew; Shemie, Sam D.; Slessarev, Marat
Abstract : Donation after circulatory determination of death has increased the number of organs available but can result in worse recipient outcomes than organs recovered from donors after neurologic death. Normothermic regional perfusion is a novel tool that can circumvent the shortcomings of donation after circulatory determination of death. However, its implementation may pose a threat to existing laws surrounding death declaration. Here, we propose a research agenda that will allow this technology to be introduced within current Canadian organ donation frameworks.